2020
DOI: 10.17586/2220-8054-2020-11-2-176-182
|View full text |Cite
|
Sign up to set email alerts
|

Electronic transport in penta-graphene nanoribbon devices using carbon nanotube electrodes: A computational study

Abstract: Electronic transport properties of pristine, homogenously and heterogeneously boron-nitrogen doped saw-tooth penta-graphene nanoribbon (SPGNR) with carbon nanotube electrodes have been studied using Extended Huckel Theory in combination with the non-equilibrium Green's function formalism. CNT electrodes produce a remarkable increase in current at higher bias voltages in pristine SPGNR. The current intensity is maximum at higher bias voltages, while the nitrogen-doped model shows current from the onset of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…[19,186] Extended Hückel theory continues to be used, [187][188][189][190][191] but certainly less so than it its heyday. In 2020 and 2021, there are at least 12 [192][193][194][195][196][197][198][199][200][201][202][203] and six publications using eHT calculations, [187][188][189][190][191]204] respectively.…”
Section: Skepticism Of the Extended Hückel Theorymentioning
confidence: 99%
“…[19,186] Extended Hückel theory continues to be used, [187][188][189][190][191] but certainly less so than it its heyday. In 2020 and 2021, there are at least 12 [192][193][194][195][196][197][198][199][200][201][202][203] and six publications using eHT calculations, [187][188][189][190][191]204] respectively.…”
Section: Skepticism Of the Extended Hückel Theorymentioning
confidence: 99%
“…Different layers or different shapes of penta-graphene have been the focus of current research, for example, single-layer penta-graphene, double-layer penta-graphene, 8 penta-graphene nanotubes, [9][10][11] and penta-graphene nanoribbons. 12,13 In addition to the intrinsic properties of penta-graphene, its modification and doping are also hot issues. It has been shown that penta-graphene doped with boron and nitrogen can be used as a high-performance material for H 2 decomposition and storage.…”
Section: Introductionmentioning
confidence: 99%